Controlling MoO2 and MoO3 phases in MoOx/CNTs nanocomposites and their application to anode materials for lithium-ion batteries and capacitors. (20th August 2021) - Han, Daseul; Hwang, Sooyeon; Bak, Seong-Min; Nam, Kyung-Wan
Graphical abstract: Image, graphical abstract Abstract: Molybdenum oxides (MoO2 and MoO3 ) are attractive anode materials for Li- and Na- ion batteries. Although there have been extensive studies on them individually, systematic and comparative studies are still lacking. In this work, we demonstrate a facile and straightforward synthesis method to control the phase and oxidation state in the MoOx /CNTs nanocomposites via hydrothermal reaction followed by heat-treatment. By changing the gas atmosphere during the annealing process, well-dispersed MoO2 /CNTs and MoO3 /CNTs nanocomposites are formed without altering their overall morphology. This strategy enables us to investigate the true structure-property correlation of MoOx /CNTs nanocomposites by comparing the structure and electrochemical properties of MoO2 /CNTs and MoO3 /CNTs. When tested as anode materials for lithium-ion batteries, both HT-MoO2&3 /CNTs electrodes show much-improved cycling stability and rate performance compared to the rod-shaped bulk MoO3 electrode. In situ Mo K-edge x-ray absorption spectroscopy (XAS) has been further employed to compare and elucidate Li + storage mechanisms of both electrodes. When employed to the negative electrode of a high-power lithium-ion capacitor (LIC), the LIC full-cell composed of HT-MoO3 /CNTs negative and activated carbon positive electrodes demonstrates impressive energy and power densities (~ 90 Wh kg −1 with 2000 W kg −1 ) and excellent cycling stability (96.8 % capacity retention after 300 cycles), revealing the versatility of the MoOx /CNTs electrodes in energy applications.